Food guide for soccer : tips and recipes from the pros - Averbuch, Gloria , 1951-; Clark, Nancy , 1951- (Meyer & Meyer Sport, 2010)
A how to food guide that addresses the nutrition questions and concerns of soccer athletes of different ages and abilities. It answers such food questions as: What should I eat before a game? What about sports drinks? How much protein should I be eating? It offers practical tips and debunks nutrition myths